মুক্তির সংগ্রাম - আনিসুজ্জামান.; বণিক, সুবলকুমার.; হোসেন, মোবারক.; দেব, দেবাশীষ.; সোম, বীরেন 1948-; চন্দ্রাবতী একাডেমী. (ঢাকা : চন্দ্রাবতী একাডেমী, 2012)
Articles on the history of freedom movements in undivided Bengal, India and Bangladesh, from 1757 to 1971.
In Bengali.
Keywords: Bengal (India) -- History; Bangladesh -- History; Bengal (India) -- Politics and government; Bangladesh -- Politics and government